2017
DOI: 10.1177/1179551417746957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of FreeStyle Libre Flash Glucose Monitoring System on Glycemic Control, Health-Related Quality of Life, and Fear of Hypoglycemia in Patients with Type 1 Diabetes

Abstract: Background/objectives:In the current era of modern technology and the development of smart devices such as the flash glucose monitoring (FGM) systems, patients can easily monitor their glucose levels more frequently without any inconvenience. In this study, we evaluate the effect of FreeStyle Libre FGM system on glycemic control, hypoglycemia, health-related quality of life (QoL), and the fear of hypoglycemia (FOH) among children and young people with type 1 diabetes (T1D).Design and methods:A prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
80
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 26 publications
(40 reference statements)
11
80
1
6
Order By: Relevance
“…In addition to previous reports, this is to our knowledge the first randomized controlled trial to evaluate the non‐adjunctive use of isCGM in the pediatric population with T1D. Two previous randomized controlled trials in adult patients with diabetes demonstrated safety and efficacy of isCGM to replace SMBG .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition to previous reports, this is to our knowledge the first randomized controlled trial to evaluate the non‐adjunctive use of isCGM in the pediatric population with T1D. Two previous randomized controlled trials in adult patients with diabetes demonstrated safety and efficacy of isCGM to replace SMBG .…”
Section: Discussionmentioning
confidence: 77%
“…The sensor‐based flash glucose monitoring system (FreeStyle Libre, Abbott Diabetes Care), an isCGM device can be scanned as often as needed with the reader displaying current sensor glucose level, glucose trend arrow and graphs of the glucose readings over the previous 8 hours; furthermore, it does not require finger‐stick calibration, as it is calibrated in the factory, and has a wear period of 14 days (10 days and a 12‐hour warm‐up period in the United States) . Recently published data have demonstrated safety and efficacy of isCGM technology to replace SMBG in adult patients with diabetes and good accuracy results in pediatric and adolescent population with T1D, with little data on benefit in glycemic control in this population . The aim of the present study was to evaluate efficiency and safety of isCGM as a replacement for standard SMBG‐based glucose control in children with type 1 diabetes (T1D) during a summer camp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is noteworthy about this system is that self-monitoring of blood glucose is not required during the 14-day wearing period. Several studies have shown the accuracy of interstitial glucose measurements, and the usefulness and safety of FGM [5][6][7][8][9][10][11] . Furthermore, it has been shown that the use of FGM reduced hypoglycemia in patients with type 1 and type 2 diabetes mellitus, although the effects of FGM on glycemic control are controversial 7,8,[12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the accuracy of interstitial glucose measurements, and the usefulness and safety of FGM [5][6][7][8][9][10][11] . Furthermore, it has been shown that the use of FGM reduced hypoglycemia in patients with type 1 and type 2 diabetes mellitus, although the effects of FGM on glycemic control are controversial 7,8,[12][13][14][15] . However, in most of the earlier studies, capillary blood glucose, not venous blood glucose, was used as a reference, and the accuracy of glucose measurements by FGM has not been fully determined 5,6,9,10,16 .…”
Section: Introductionmentioning
confidence: 99%